A Global Perspective on the Role of Faith and Spirituality in a Post-COVID-19 National and Community Recovery: The Nigeria Case of the Pandemic - Odion, Omogbai Ehimikhuae (European Scientific Journal, ESJ, 2022)
This paper focuses on contributing to the ongoing discourse regarding the global perspectives on the role of faith and spirituality in a post-COVID-19 national and community recovery with reference to the pandemic in Nigeria. The year 2020 saw a lot of faith organisations like churches introduce and apply new initiatives of spirituality-based elements in helping people to recover from the pandemic. These elements are embodied in their programs and fellowships to their members and the general society. A vast majority of the members acknowledge a reliance on God for solutions against mental, emotional, physical, material, and financial challenges caused by the pandemic. An analytical methodology through the Integrated Critical Analysis method was used with data collected from available literature as tools of research for this study. The research findings of this study show that the value and benefit of faith includes its efficacy on the behaviours and attitude displayed in the engagement or non-engagement of people. This is to the extent of the people’s faith, religious and spiritual beliefs, along with the support that they find in their being members of faith communities. Although people may have at one time or the other had negative experiences in the past, however, studies show that faith and spirituality plays a significant role in preventing further negative effects and risk in the recovery process. The study concludes that the value that spirituality and faith-oriented approaches bring to the prevention and recovery process is a necessity.